The Transformation Of Shari'ah Economy Through Islamic Finance In The Digital Era For A Sustainable Future - Kuswara, Lalu Indra Wadi Kuswara (Universitas Islam Negeri Mataram, 2025)
The rapid growth of the global economy, especially in the digital era, has brought both challenges and opportunities in achieving sustainable economic development. In this context, the sharia economy, which is based on the principles of justice, sustainability, and collective benefit, has significant potential as a relevant solution. One of the key components of the sharia economy is Islamic finance, which operates based on sharia principles, such as the prohibition of riba (interest), gharar (uncertainty), and maysir (gambling), and emphasizes social responsibility. Digital transformation is not merely a trend but a necessity to meet the demands of a rapidly evolving market and the increasingly complex global financial ecosystem. In the context of Islamic finance, fintech plays an increasingly important role in facilitating growth and transformation through services such as sharia peer-to-peer financing, investment platforms, and sharia-based financial applications. This study aims to explore how Islamic finance can contribute to transforming the sharia economy toward a more sustainable future in the digital era. Using a qualitative literature review method, this article analyzes the role of fintech in accelerating the application of sharia-compliant financial solutions that are environmentally friendly and sustainable. The findings highlight that the integration of technology in sharia finance not only increases efficiency and transparency but also supports broader financial inclusion and sustainability.